CAREER AFTER RETIREMENT: A COMPARISON BETWEEN FORMER FEMALE AND MALE ATHLETES IN HOCHIMINH CITY – VIETNAM - Nguyen Hoang Minh Thuan (Innovative Journal of Medical and Health Sciences, 2019)
The results showed that most athletes retire for reasons such as: anxiety for future careers, no achievements, injuries.... After retirement, they receive the assistance form many individuals and organizations. Many former male athlete work in sport field, their income is also better former female athlete; Although income is the most common trait that former female athletes choose to work. Keywords: Difference, former athlete, career, retirement